2012
DOI: 10.1590/s0370-44672012000200018
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionamento estrutural de estradas de mina a céu aberto

Abstract: Uma estrada de mina foi dimensionada com materiais típicos ocorrentes em mineração de minério de ferro no Brasil, utilizando-se os métodos empíricos CBR e DNER. Através do programa de dimensionamento estrutural mecanístico-empírico ELSYM5, compararam-se os resultados obtidos pelos métodos anteriores e propôs-se a otimização do dimensionamento feito pelo método DNER. Os resultados mostram que a espessura total do pavimento calculada pelos dois métodos é, basicamente, a mesma, sendo que a espessura da camada de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
0
4
0
3
Order By: Relevance
“…With the ratification of the results of this research for conventional trucks, whose hypothesis of convergence of load equivalency factors is sustainable, even with the variation of the parameters of the deflection analysis at the top of the subgrade, it is observed that Sousa (2011) extended the curve of the abacus Axle Load versus LEF presented in DNIT (2006) using mathematical regression, finding the value of 1,640,000 for LEF relative to 167 tons for single axle with twin wheels, through Equation 2, where C is the axle load, in tons. LEF = 0.001×C 4.5951 (2)…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…With the ratification of the results of this research for conventional trucks, whose hypothesis of convergence of load equivalency factors is sustainable, even with the variation of the parameters of the deflection analysis at the top of the subgrade, it is observed that Sousa (2011) extended the curve of the abacus Axle Load versus LEF presented in DNIT (2006) using mathematical regression, finding the value of 1,640,000 for LEF relative to 167 tons for single axle with twin wheels, through Equation 2, where C is the axle load, in tons. LEF = 0.001×C 4.5951 (2)…”
Section: Resultsmentioning
confidence: 84%
“…In iron ore mines that operate on a large-scale, ore transport is usually made by trucks with high axle load capacity. According to Sousa (2011), roads in open pit mines are typically designed by mine planning professionals and executed by operating or infrastructure teams. Unlike the treatment given to highways, Brazilian standards concerning mining activities do not include technical parameters for road design, focusing on regulations directed towards worker safety.…”
Section: Load Equivalency Factors For Off-road Trucksmentioning
confidence: 99%
See 2 more Smart Citations
“…(THOMPSON, 2014). Sousa, et al (2012), afirmam que o planejamento de estradas de transporte em uma mina, geralmente é realizado por profissionais da área de planejamento de lavra e estruturado por equipe da operação de mina. Essas estradas, que são as principais linhas de acesso ao transporte do minério e estéril, são de grande relevância e os efeitos prejudiciais da concepção inadequada das estradas de transporte, gerenciamento e manutenção estão se tornando cada vez mais evidentes.…”
Section: Metodologiaunclassified